1979
DOI: 10.1159/000145035
|View full text |Cite
|
Sign up to set email alerts
|

Micro-indentation hardness studies on human bones

Abstract: Bones from different portions of human skeleton are polished and cut to suitable sizes and then subjected to micro-indentation at various loads using Vicker’s diamond pyramidal indenter. The Vicker’s hardness number is found to differ slightly from portion to portion of the skeleton. Interferometric studies of the indentation reveal that the applied stress of indentation causes a ‘pile-up’ of material near the corners of the pyramidal indents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
1
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 1 publication
4
15
1
1
Order By: Relevance
“…Among the first studies of the mechanical properties of fingernails, Baden [204] reported elastic modulus values from experimental cut tests and by measuring the velocity of sound in nail plate ($2-4.3 GPa); Ramrakhiani [207] showed that spherical indents on the nail surface recovered over a period of time. Tensile testing on fingernails along the axis of fibers in intermediate layer yielded a strength of 86 MPa under ambient environment.…”
Section: Nailsmentioning
confidence: 99%
“…Among the first studies of the mechanical properties of fingernails, Baden [204] reported elastic modulus values from experimental cut tests and by measuring the velocity of sound in nail plate ($2-4.3 GPa); Ramrakhiani [207] showed that spherical indents on the nail surface recovered over a period of time. Tensile testing on fingernails along the axis of fibers in intermediate layer yielded a strength of 86 MPa under ambient environment.…”
Section: Nailsmentioning
confidence: 99%
“…However, one study reported an increase in Vicker's hardness for weights below 50 g [30]. In addition, pile up was observed in the latter study for loads above 100 g. Hardness was generally found to be homogeneous [26,30], but along a long bone, hardness tended to be higher in the diaphysis than in the meta-and epiphysis [4,35,40,45]. Hardness of trabecular bone was shown to be somewhat lower (10-15%) than the interstitial bone of the adjacent cortex [20,45].…”
Section: Tissue Hardnessmentioning
confidence: 99%
“…These were formed from 50 g loading. Loading with lesser weight will result in smaller deformation "squares"; however, at the expense of uniform indent properties [16]. Even 25 g loading, however, would not have produced substantially smaller indents (14-18 ~tm squares).…”
Section: Discussionmentioning
confidence: 99%
“…1): newly-formed endocortical and periosteal bone, and anterior, lateral, medial and posterior preexisting ("extant") bone_ The three measurements per region produced a range of values that, on average, was only 34% of the range of values among all femora from one group. A 50g load, selected to ensure uniform measurements that are less prone to variance due to bone heterogeneity [16], was applied for at least 10 s to ensure complete indent deformation [11]. A separation distance of at least one indent diameter was maintained between the indent sites, sample edges and visible osteocytes and lacunae in order to minimize undesired edge effects [11].…”
Section: Methodsmentioning
confidence: 99%